GCHF basis sets and their application in the electronic structure study of PrMnO3 - Treu, O.; Pinheiro, J. C.; Kondo, R. T.; Jafelicci, M. (Elsevier B.V., 2004)
The approach called generator coordinate Hartree-Fock (GCHF) method is used in the selection of Gaussian basis set [25s18p for O ((3)p), 31s21p14d for Mn (S-6), and 33s22p16d9f for Pr ((4)J)] for atoms. The role of the weight functions in the assessment of the numerical integration range of the GCHF equations is shown. These basis sets are contracted to (25s18p/9s5p), (31s21p14d/9s6p4d), and (33s22pl6d9f118sl2p5d3f) by segmented contraction scheme of Dunning and they are utilized in calculations of Restricted-Open-HF (ROHF) Total and Orbital energies of the (MnO+1)-Mn-3 and (PrO+1)-Pr-1 fragments, to evaluate their quality in molecular studies. The addition of one d polarization function in the contracted (9s5p) basis set for O(P-3) atom and their application with the contracted (9s6p4d), (18s21p5d3f) basis sets for Mn (S-6) and Pr-Pr ((4)j) atoms lead to the electronic structure study of PrMnO3. The dipole moment, the total energy, and total atomic charges properties were calculated and were carried out at ROHF level with the [PrMnO3](2) fragment. The calculated values show that PrMnO3 does not present piezoelectric properties. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: generator coordinate Hartree-Fock basis sets; contracted basis sets; electronic structure of PrMnO3; piezoelectric